Ophthalmic pH Sensitive In-Situ Gel: A Review: A REVIEW : OPHTHALMIC PH SENSITIVE IN SITU GEL - Garge, Lajri Vasant; Saudagar, Ravindranath (Journal of Drug Delivery and Therapeutics, 2019)
Ocular Drug Delivery has been a major challenging and interesting field for the pharmaceutical scientist due to unique anatomy and physiology of eye. The eye suffers from various problems like glaucoma, dry eye syndrome, keratitis, endopthalmitis, trachoma and conjunctivitis. To achieve the effective ocular therapy within the eye. An adequate amount of active ingredients must be delivered and maintained at the site of action. The conventional therapy exhibits the poor bioavailability due to the rapid precorneal drug loss. There are some static and dynamic barriers which also affect the bioavailability of drug. There are considerable efforts which are directed towards newer drug system for ocular administration to overcome the drawbacks of conventional therapy. The use of in situ overcomes the problems when drop instilled into the eye it undergoes sol-gel transition and transition form in cul-de-sac. This review involves in-situ gel system which includes thermally triggered system, pH triggered system and ion cross linking system. It involves detailed method of preparation and evaluation parameters of pH triggered system. Keywords: Ocular Drug Delivery, in-situ gel, pH sensitive, temperature sensitive, ion sensitive.